Tea a mirror of soul ; [opera in three acts] - Tan, Dun 1957- (Dt. Grammophon, 2004)
A tragic love story of Seikyo (Japanese prince/monk) for Chinese Princess Lan.
Interpr. u.a.: Haijing Fu [Japanese prince/Monk.] Nancy Allen Lundy [Chinese princess/Puppet monk]. Christopher Gillett [Chinese prince/Puppet monkey king]. Bass-baritone Chorus of the Netherlands Opera. NHK Symphony Orchestra. Tan Dun [Dir.]. Pierre Audi [Bühnenegie]. - Live-Aufn.: Tokyo, Suntory Hall, 22. Oktober 2002. - P-Jahre: 2002 und 2004. - Gesungen in engl. Sprache. - Text des Beih.: engl., dt., franz. - Untertitel: engl., franz., dt., span., chin. - Bonus: Tan Dun video clips. The map showreel. Trailer
Keywords: Operas; DVD-Video